Maternal vitamin D status in early pregnancy and its association with gestational diabetes mellitus in Shanghai: a retrospective cohort study - Yan Cheng; Jiayuan Chen; Tingting Li; Jiangnan Pei; Yongfang Fan; Mulan He; Shuangping Liu; Junxiu Liu; Qingying Zhang; Haidong Cheng (BMC, 2022)
Abstract Background There is growing interest regarding vitamin D and its potential role in gestational diabetes mellitus (GDM). We aimed to assess maternal vitamin D status in early pregnancy and its relationships with the risk of GDM in a Chinese population in Shanghai. Methods The retrospective cohort study included a total of 7816 pregnant women who underwent a 75-g oral glucose tolerance test (OGTT) during 24-28 weeks of gestation. Participants' demographic information including maternal age, prepregnancy body mass index (BMI), gestational age, parity, season of blood collection, serum 25-hydroxy vitamin D [25(OH)D] data and other blood biomarker data at 6 to 14 weeks of gestation were retrospectivly extracted from the medical records in the hospital information system. Results In the cohort, the prevalence of GDM was 8.6% and the prevalence of vitamin D deficiency and insufficiency in early pregnancy was 53.1 and 38.5%, respectively. The mean value of the serum 25(OH)D concentration was 19.6±7.5 ng/mL. The restricted cubic splines model showed an inverted J-shaped relationship in which the risk of GDM decreased when the 25(OH)D concentrations were ≥ 20 ng/mL. Logistic model analysis showed that 25(OH)D concentrations ≥ 30 ng/mL significantly decreased the risk of GDM (odds ratio = 0.63, 95% confidence interval: 0.45-0.89; P = 0.010) compared with 25(OH)D concentrations < 20 ng/ml. Conclusions In early pregnancy, vitamin D deficiency and insufficiency were very common, and a high level of vitamin D showed protective effects against the incidence risk of GDM.